The mammosphere-derived epithelial cell secretome modulates neutrophil functions in the bovine model - Harman, Rebecca M.; Sipka, Anja; Oxford, Kelly A.; Oliveira, Leane; Huntimer, Lucas; Nydam, Daryl V.; Van de Walle, Gerlinde R. (Frontiers in Immunology, 2024)
Background: Innovative therapies against bacterial infections are needed. One approach is to focus on host-directed immunotherapy (HDT), with treatments that exploit natural processes of the host immune system. The goals of this type of therapy are to stimulate protective immunity while minimizing inflammation-induced tissue damage. We use non-traditional large animal models to explore the potential of the mammosphere-derived epithelial cell (MDEC) secretome, consisting of all bioactive factors released by the cells, to modulate host immune functions. MDEC cultures are enriched for mammary stem and progenitor cells and can be generated from virtually any mammal. We previously demonstrated that the bovine MDEC secretome, collected and delivered as conditioned medium (CM), inhibits the growth of bacteria in vitro and stimulates functions related to tissue repair in cultured endothelial and epithelial cells. Methods: The immunomodulatory effects of the bovine MDEC secretome on bovine neutrophils, an innate immune cell type critical for resolving bacterial infections, were determined in vitro using functional assays. The effects of MDEC CM on neutrophil molecular pathways were explored by evaluating the production of specific cytokines by neutrophils and examining global gene expression patterns in MDEC CM-treated neutrophils. Enzyme linked immunosorbent assays were used to determine the concentrations of select proteins in MDEC CM and siRNAs were used to reduce the expression of specific MDEC-secreted proteins, allowing for the identification of bioactive factors modulating neutrophil functions. Results: Neutrophils exposed to MDEC secretome exhibited increased chemotaxis and phagocytosis and decreased intracellular reactive oxygen species and extracellular trap formation, when compared to neutrophils exposed to control medium. C-X-C motif chemokine 6, superoxide dismutase, peroxiredoxin-2, and catalase, each present in the bovine MDEC secretome, were found to modulate neutrophil functions. Conclusion: The MDEC secretome administered to treat bacterial infections may increase neutrophil recruitment to the site of infection, stimulate pathogen phagocytosis by neutrophils, and reduce neutrophil-produced ROS accumulation. As a result, pathogen clearance might be improved and local inflammation and tissue damage reduced.